Sarcolemma resilience and skeletal muscle health require O-mannosylation of dystroglycan - Jeffrey M. Hord; Sarah Burns; Tobias Willer; Matthew M. Goddeeris; David Venzke; Kevin P. Campbell (Skeletal Muscle)
Abstract Background Maintaining the connection between skeletal muscle fibers and the surrounding basement membrane is essential for muscle function. Dystroglycan (DG) serves as a basement membrane extracellular matrix (ECM) receptor in many cells, and is also expressed in the outward-facing membrane, or sarcolemma, of skeletal muscle fibers. DG is a transmembrane protein comprised of two subunits: alpha-DG (α-DG), which resides in the peripheral membrane, and beta-DG (β-DG), which spans the membrane to intracellular regions. Extensive post-translational processing and O-mannosylation are required for α-DG to bind ECM proteins, which is mediated by a glycan structure known as matriglycan. O-mannose glycan biosynthesis is initiated by the protein O-mannosyltransferase 1 (POMT1) and POMT2 enzyme complex and leads to three subtypes of glycans called core M1, M2, and M3. The lengthy core M3 is capped with matriglycan. Genetic defects in post-translational O-mannosylation of DG interfere with its receptor function and result in muscular dystrophy with central nervous system and skeletal muscle pathophysiology. Methods To evaluate how the loss of O-mannosylated DG in skeletal muscle affects the development and progression of myopathology, we generated and characterized mice in which the Pomt1 gene was specifically deleted in skeletal muscle (Pomt1skm) to interfere with POMT1/2 enzyme activity. To investigate whether matriglycan is the primary core M glycan structure that provides the stabilizing link between the sarcolemma and ECM, we generated mice that retained cores M1, M2, and M3, but lacked matriglycan (conditional deletion of like-acetylglucosaminyltransferase 1; Large1skm). Next, we restored Pomt1 using gene transfer via AAV2/9-MCK-mPOMT1 and determined the effect on Pomt1skm pathophysiology. Results Our data showed that in Pomt1skm mice O-mannosylated DG is required for sarcolemma resilience, remodeling of muscle fibers and muscle tissue, and neuromuscular function. Notably, we observed similar body size limitations, sarcolemma weakness, and neuromuscular weakness in Large1skm mice that only lacked matriglycan. Furthermore, our data indicate that genetic rescue of Pomt1 in Pomt1skm mice limits contraction-induced sarcolemma damage and skeletal muscle pathology. Conclusions Collectively, our data indicate that DG modification by Pomt1/2 results in core M3 capped with matriglycan, and that this is required to reinforce the sarcolemma and enable skeletal muscle health and neuromuscular strength.